The fundamental complex of Western Damaraland, South West Africa - Gevers, Traugott Wilhelm (Department of Geological Sciences, 2016)
Enormous areas of South West Africa, particularly in its central portion, are occupied by very ancient gneissoid and granitic rooks, a great variety of schists and other more or less highly metamorphosed sediment. These ancient rooks, forming as they do the backbone or nucleus of our continent, on which all younger rocks repose as a veneer of varying thickness and continuity are everywhere generally grouped together under the term Basement or Fundamental Complex. For obvious reasons, chief of which are their invariably highly folded and metamorphosed nature and the entire absence of fossils, these ancient sediments and their intrusives have nearly always after the first initiation of geological surveys in most countries of Africa been somewhat neglected and also visiting geologists have generally preferred to devote their attention and limited time to less complex problems, for the solution of which detailed mapping extended over many years was not an essential or indeed a sine qua non. A notable exception, however, to this rule is the detailed early work of Rogers and Du Toit in the northern Cape and of Hall in the eastern and northeastern Transvaal.